L’association comme réponse à la question sociale du XIXe au XXe siècle : - Anne Fretel (Revue de la Régulation)
Since the XIXth century, in France, the “social question” is crucial to the debate over economic and social reforms. The debate is mainly structured around the following alternative: to reinforce economic liberalism or to recognise a widened role for State intervention. If the “social question” has been polarized by these two types of answers, other institutions were also introduced: associations. Yet, this article shoes that, while developing the notion of association, thinkers did not develop a specific answer to the ‘social question’. Indeed, we argue that their analysis can be linked either to the logic of economic liberalism or to the logic of state intervention. Doing so, the article proposes to differentiate two periods: during the XIXth century, associations lie within the framework of economic liberalism whereas during the XXth century, associations are rather envisaged within the scope of the Welfare State. The historical perspective introduced helps us shed new light on the contemporary tension between economic liberalism and welfare state approaches to associations – whereas such tension can not be overcome if we stick to an analysis of the social economy in the field of reciprocity as is usually the case.